AUTHENTIC VIDEO AND SUBTITLES ON ENGLISH VOCABULARY ENHANCEMENT (A Quasi-Experimental Study in One Private College in Bandung) - Siska Rizkiani (Eltin Journal : Journal of English Language Teaching in Indonesia, 2015)
Video is commonly used in instructional settings. The mixture of sound, image, and text -in the form of subtitles- has valued the video. It considers video as an understandable media for teaching vocabulary to foreign language students. This study is aimed at finding the effectiveness of using authentic video and subtitles in EFL teaching learning. This study is conducted at one of private colleges in Bandung. It is an experimental study. It compares the result of pre-test and post-test given to the students. The result of the t-test is the score in the t-test table (2.03 and 2.75) is smaller than the score obtain in this study (13.52), so the alternative hypothesis is accepted and the null hypothesis is rejected. It means that using authentic video and subtitles in teaching English vocabulary is effective.Keywords: Authentic Video, Vocabulary, Subtitles